Nutritional status and dietary adequacy amid reproductive aged women in Cumilla, Bangladesh - Islam, Md Hafizul; Jubayer, Ahmed; Nayan, Md Moniruzzaman (Asian Journal of Medical and Biological Research, 2021)
Dietary patterns are evolving greatly during the last years and various diet and lifestyle related diseases are increasing day by day. The prevalence of double burden of malnutrition and various nutritional deficiency diseases among the reproductive aged women, the most vulnerable group has become a severe concern during the last decades. Therefore, the study focused on the nutritional status of reproductive aged women, their dietary food and nutrient intake and the adequacy of these consumed nutrients as compared to their requirements. A cross-sectional study was conducted among the randomly selected 355 households in Cumilla district in Bangladesh. The results showed that only about 32% of the participants were found having a normal BMI range. The percentage of underweight, overweight and obesity among the participants were 13.3% (95% CI: 10.25, 16.36), 35.8% (95% CI: 31.49, 40.12) and 19.6% (95% CI: 16.04, 23.17) respectively. Dietary protein, carbohydrate, total fat consumption was 11.87%, 65.22% and 18.9% of energy. Consumption of vitamin A, C, D, Folic acid, calcium, sodium, riboflavin and potassium was very poor and found below EAR/AI among the most respondents. Thiamin, zinc, iron, phosphorous intake was satisfactory among the most respondents. Asian J. Med. Biol. Res. December 2020, 6(4): 628-634